Empirical Evidence on the Long-Run Neutrality Hypothesis Using Divisia Money - Tang, Maggie May-Jean; Puah, Chin Hong; Dayang Affizzah, Awang Marikan (International Academy of Business and Economics, 2013)
By employing Fisher and Seater’s (1993) long-run neutrality test, the researchers tested the monetary neutrality proposition in Singapore for the period of 1980-2009. Empirical findings show that monetary neutrality does not hold in Singapore when both the simple-sum money and Divisia money are employed. As both the simple-sum and Divisia monetary aggregates are non-neutral, monetary authorities may consider their use as a monetary policy tool affecting real economic activity.